(untitled) (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2025)
Mixed convection heat transfer in enclosures with a spinning inner cylinder has attracted considerable research interest due to its relevance in many engineering and technical applications such as electronic cooling, energy systems, and industrial thermal management. This review article presents a comprehensive overview of recent numerical investigations focused on enhancing mixed convection performance via revolving cylinders under numerous boundary and flow conditions. The enhancement techniques are systematically categorised into six main categories: nanofluids and hybrid nanofluids, porous media, ventilated cavities, moving wall enclosures, multi-cylinder configurations, and other enhancement strategies. Each group is analyzed regarding cavity geometry, thermal characteristics, and performance metrics, including Nusselt number behaviour. Summary tables are provided to facilitate comparison across studies. Key trends, limitations, and emerging gaps in the literature are highlighted, offering guidance for future study and optimization of advanced thermal systems involving spinning elements.